STZ-induced hyperglycemia differentially influences mitochondrial distribution and morphology in the habenulointerpeduncular circuit - Jodeiri Farshbaf, Mohammad; Matos, Taelor A.; Niblo, Kristi; Alokam, Yacoub; Ables, Jessica L. (Frontiers in Cellular Neuroscience, 2024)
IntroductionDiabetes is a metabolic disorder of glucose homeostasis that is a significant risk factor for neurodegenerative diseases, such as Alzheimer’s disease, as well as mood disorders, which often precede neurodegenerative conditions. We examined the medial habenulainterpeduncular nucleus (MHb-IPN), as this circuit plays crucial roles in mood regulation, has been linked to the development of diabetes after smoking, and is rich in cholinergic neurons, which are affected in other brain areas in Alzheimer’s disease.MethodsThis study aimed to investigate the impact of streptozotocin (STZ)-induced hyperglycemia, a type 1 diabetes model, on mitochondrial and lipid homeostasis in 4% paraformaldehyde-fixed sections from the MHb and IPN of C57BL/6 J male mice, using a recently developed automated pipeline for mitochondrial analysis in confocal images. We examined different time points after STZ-induced diabetes onset to determine how the brain responded to chronic hyperglycemia, with the limitation that mitochondria and lipids were not examined with respect to cell type or intracellular location.ResultsMitochondrial distribution and morphology differentially responded to hyperglycemia depending on time and brain area. Six weeks after STZ treatment, mitochondria in the ventral MHb and dorsal IPN increased in number and exhibited altered morphology, but no changes were observed in the lateral habenula (LHb) or ventral IPN. Strikingly, mitochondrial numbers returned to normal dynamics at 12 weeks. Both blood glucose level and glycated hemoglobin (HbA1C) correlated with mitochondrial dynamics in ventral MHb, whereas only HbA1C correlated in the IPN. We also examined lipid homeostasis using BODIPY staining for neutral lipids in this model given that diabetes is associated with disrupted lipid homeostasis. BODIPY staining intensity was unchanged in the vMHb of STZ-treated mice but increased in the IPN and VTA and decreased in the LHb at 12 weeks. Interestingly, areas that demonstrated changes in mitochondria had little change in lipid staining and vice versa.DiscussionThis study is the first to describe the specific impacts of diabetes on mitochondria in the MHb-IPN circuit and suggests that the cholinergic MHb is uniquely sensitive to diabetesinduced hyperglycemia. Further studies are needed to understand the functional and behavioral implications of these findings.